PERANAN BADAN USAHA MILIK GAMPONG (BUMG) DALAM MENINGKATAN PENDAPATAN PETANI PADI SAWAH DI DESA PULO DAYAH KECAMATAN GLUMPANG TIGA KABUPATEN PIDIE - Eka Agustina; Tuti Rahmah (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2021)
The Pulo Lon/Pulo Dayah Village Government formed BUMG as a driving force for the village economy but in its formation there was still minimal guidance from the Regional Government so that several problems emerged, including the differences in terms of service in Perda and Perdes, lack of socialization to the community, and lack of use of computer technology in manage BUMG. The purpose of the study was to find out how the role of Gampong-Owned Enterprises (BUMG) in Increasing Rice Farmers' Income in Pulo Lon Village / Pulo Dayah, Glumpang Tiga District, Pidie Regency. The results of the study indicate that the role of BUMG in general has been running well. This can be seen based on the good running of BUMG programs. Even though in terms of financial planning and programs it has not been managed properly so that the BUMG program has not been fully running optimally because there are several things that must be improved, such as the lack of human and financial resources as well as weak socialization and lack of coordination. Suggestions that can be given are so that there is no delay in improving the quality and quantity of human resources, increasing financial resources, socializing more evenly and improving coordination so that empowerment and the active role of the community can be increased.Keywords: Implementation, Program, BUMDes